Energy use Efficiency on High Rise Hotel Building to Reduce Carbon Emission Using Sefaira - Satriopratomo, Dhimas F.; Devia, Yatnanta Padma; Susanti, Lilya (Universitas Ibn Khaldun Bogor, 2024)
A lot of energy consumed by large hotel buildings can affect the environment degradation in a long period of time. Every building plan, including hotels must consider an integrated balance in utilizing existing and limited resources based on low CO2 emissions. Excessive use of energy has a negative impact which increasing the amount of CO2 emissions. This research aims to determine the effect of energy efficiency to provide recommendations, which require significant reduction of energy and environmental degradation by minimizing energy use and CO2 emission. The method that used in this research are modelling, and simulate the energy use intensity and carbon emission using Sefaira as a Sketchup Software plug-in by simulating the existing design and provide a recommendation. The object that being used in this research is a hotel building that have 11 floor and 1 basement in Yogyakarta, Indonesia. The result shows EUI of existing hotel building is 977 kWh/m2/year and carbon emission 1.872.042 kgCO2e/year. Comparing to the EUI standard which at the limit of 290–400 kWh/m2/yr. It is recommended to build additional window at the dismantled room area on north and south side of the hotel’s corridor. The recommended design, provides a reduction of EUI into 744,22 kWh/m2/year (31,28%). Meanwhile the carbon emission reduced into 1.467.072 kgCO2e/year (27,60%) from the existing design.